PERAN BADAN PENGAWAS PEMILU DALAM MENCEGAH POLITIK UANG ( MONEY POLITIC ) - Pakpahan, Gibson Romando; Siregar, Hisar (Lembaga Dongan Dosen, 2025)
The election supervisory agency (Bawaslu) has a crucial role in maintaining the integrity of elections in Indonesia, especially in preventing the practice of money politicts that can damage the democratic process. Money politics is a form of violation that often occurs in elections, wich can affect voters choices and create injustice. In order to prevents this practice, Bawaslu implements various prevention straregies, including socialization to the community, supervision of prospective election participants, and law enforcement against specified violation. This study aims to evaluate the effectiveness of Bawaslu efforts in preventing money politics and identifying the challenges faced. The result of the study show that although Bawaslu has carried out various initiatives, such as educational campaigns and increased public participation in supervision, challenges such as lack of public awarenes and limited recources are still significant obtacles. Therefore, it is necessary to strengthen the capacity of Bawaslu and collaborate with other institutions to create a cleaner and more transparent electon environment. Thus, effort to prevent money politics by Bawaslu are expected to produce a more democratic and fair one for all Indonesian people.